Acoustic Startles in Horror Films: A Neurofilmological Approach. Issue 1 (1st March 2019) - Sbravatti, Valerio
Abstract : The acoustic blast is one of the most recurrent sound devices in horror cinema. It is designed to elicit the startle response from the audience, and thus gives them a "jump scare." It can occur both in the form of a diegetic bang and in the form of a nondiegetic stinger (i.e., a musical blare provided by the score). In this article, I will advance the hypothesis that silence plays a crucial role in contemporary horror films, both perceptually, since it leaves the sound field free for the acoustic blast, and cognitively, since it posits the audience in an aversive anticipatory state that makes the startle more intense. I will analyze the acoustic startle using a neurofilmological approach, which takes into account findings from experimental sciences in order to better understand the relationship between physiological and psychological factors that make such an effect possible during the filmic experience.